1996
DOI: 10.1111/j.1945-5100.1996.tb02017.x
|View full text |Cite
|
Sign up to set email alerts
|

New fission‐track age determinations on impact glasses

Abstract: Abstract— Four samples from Libyan Desert glass, one sample from Muong‐Nong‐type tektite, labelled Guang‐Dong, and one sample from Czech Moldavite were analysed using the fission‐track dating method. The Moldavite was unaffected by partial thermal track annealing, whereas the ages of Libyan Desert glass and Guang‐Dong tektite appear to have been thermally lowered. Fission‐track ages of the latter impact glasses were corrected using the plateau method. Apparent ages of Libyan Desert glass (between 26.0 ± 1.8 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 10 publications
2
28
0
1
Order By: Relevance
“…In terms of chemical composition, LDG is very silica-rich (approximately 98 wt% of SiO 2 content) and has low abundances of most major oxides. The age of LDG was determined by fission-track analysis giving ages ranging from 28.5 ± 2.3 Ma to 29.4 ± 0.5 Ma (plateau age) (e.g., Bigazzi and de Michele 1996;Horn et al 1997). The origin of LDG has been the subject of much debate since it was discovered early in the 20th century.…”
Section: Samplesmentioning
confidence: 99%
“…In terms of chemical composition, LDG is very silica-rich (approximately 98 wt% of SiO 2 content) and has low abundances of most major oxides. The age of LDG was determined by fission-track analysis giving ages ranging from 28.5 ± 2.3 Ma to 29.4 ± 0.5 Ma (plateau age) (e.g., Bigazzi and de Michele 1996;Horn et al 1997). The origin of LDG has been the subject of much debate since it was discovered early in the 20th century.…”
Section: Samplesmentioning
confidence: 99%
“…According to isotope and fission track studies LDG formed about 29 million years ago (e.g., Gentner et al 1969;Mu¨ller-Sohnius et al 1993;Bigazzi and de Michele 1996), most likely during an asteroid impact that caused shock-induced melting of Nubian sandstone Kleinmann et al 2001) or sandy material derived from a Precambrian crystalline basement (Schaaf and Mu¨ller-Sohnius 2002). This view is strengthened by the finding of shock metamorphic features present in sandstones from the Libyan Desert Glass strewn field (Kleinmann et al 2001;C.…”
Section: Introductionmentioning
confidence: 99%
“…40 Ar/ 39 Ar Dating 40 Ar/ 39 Ar analyses were performed on a single moldavite specimen that had previously undergone FT dating (Bigazzi and De Michele 1996;Balestrieri et al 1997;Balestrieri et al 1998;Bouška et al 2000); the original weight of the samples is reported in Table 1. Pieces of green moldavites were lightly crushed in an agate mill, and small chips with no visible bubbles or surface alteration were selected under a microscope for analysis.…”
Section: Analytical Data Samplesmentioning
confidence: 99%